How is parenting stress related to parental burnout among children’s mothers in China: the mediating role of marital satisfaction and the moderating role of socioeconomic status - Xu, Xiaoyan; Hanafi, Zahyah; Zhang, Shun (Frontiers in Public Health, 2024)
IntroductionAlthough parenting is a worthwhile and joyful process, it can also cause stress, potentially leading to parental burnout. With the implementation of the three-child policy in China, more parenting hours and higher economic costs may increase the risk of parental burnout.ObjectivesThis study investigated how was maternal parenting stress related to mothers’ parental burnout, as well as the potential mediating effect of their marital satisfaction and the moderating effect of their socioeconomic status on this relationship.MethodsData were collected from 314 mothers living in mainland China. The Chinese versions of the Parenting Burnout Assessment Scale, Parenting Stress Index, and Marriage Perception Scale were used to measure mothers’ parental burnout, parenting stress, and marital satisfaction.ResultsMothers‘ parenting stress was significantly and positively related to mothers’ parenting burnout. Mothers’ marital satisfaction mediated this relationship. Mothers’ socioeconomic status moderated the first half of the mediation model, and parenting stress exhibited a greater effect on marital satisfaction when mothers had a higher socioeconomic status.DiscussionThese findings indicated that mothers’ parenting stress could be alleviated by increasing marital satisfaction, which, in turn, reduced the risk of parental burnout. Furthermore, socioeconomic status may enhance the negative effects of parenting stress on marital satisfaction among mothers.